The Rigor Revolution in Impact Assessment: Implications for CGIAR - Stevenson, James R.; Macours, K.; Gollin, D. (CGIAR Independent Science and Partnership Council, 2018)
This synthesis study highlights major changes in methodology and standards of evidence in impact assessment that have taken place over the past decade, taking as its starting point the publication of the landmark report When will we ever learn? Improving lives through impact evaluation by the Center for Global Development (CGD).